Validitas Media Pori (Podcast Ruang Bicara) Dalam Meningkatkan Self Esteem Siswa SMA - Larasati, Indri Novia; Muwakhidah, Muwakhidah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2023)
This study aims to increase students' self-esteem based on the urgency of the problems felt by teenagers at the high school level. The research model applied is the Borg and Gall Research and Development procedure. The procedure consists of three steps, namely preliminary studies, planning and development of media products and product testing. At the product test stage, two tests were carried out, namely the expert test and the prospective user test. Collecting data using an acceptability questionnaire as an assessment of media products and a self-esteem questionnaire as an assessment. The results of the PORI media research meet the criteria for accuracy, use, through the results of expert tests and prospective users. However, this research stops at the stage of potential users not reaching a limited group. The average obtained through the media and content expert test is 1, meaning that this media has very good acceptability and is grateful in theory. The results of the prospective user test on 60 respondents from high school students have a high category with a score of 80% of 48 respondents, a medium category of 18.3% of 11 respondents, and a low category of 1.6% of 1 respondent. So it can be said that the PORI media is grateful in increasing the self-esteem of high school students